Fibromigraine: a new name for an old disease? - Silva, Louana C.; Oliveira, Daniella A.; Martins, Hugo A. L.; Medeiros, Fabiola L.; Araújo, Lúcia C. L.; Serva, Waldmiro A. D.; Costa Neto, Joaquim J. S.; Medeiros, Paloma L.; Silva, Simone C. S.; Carvalho, Marise F. L.; Sampaio, Maria da Conceição; Couceiro, Tânia C. M.; et al. (Headache Medicine, 2011)
Fibromyalgia and migraine are common disorders that predominantly affect women and seem to share the same pathophysiological mechanisms. We reviewed common aspects of the pathophysiology regarding pain control mechanisms and neuroendocrine dysfunction occurring in fibromyalgia and migraine. We also discuss the participation of hypothalamic and brainstem centers of pain control, the putative role played by neurotransmitters or neuromodulators on central sensitization, and changes in their levels in the cerebrospinal fluid. Because of the reasons exposed we could start considering the combination of two diseases - fibromigraine - as an individual clinical condition considered a different disorder from those found in patients suffering of migraine or fibromyalgia separately. In a preliminary study involving 41 women with migraine, 4 subgroups were analyzed: control (migraine alone), patients with migraine and fibromyalgia (fibromigraine), and other two groups when only one of the two criteria of fibromyalgia was observed, as migraine associated to chronic corporal pain during more than three months (partial fibromyalgia with just a few painfull points) and migraine associated with diffuse hyperalgesia (partial fibromyalgia without any chronic corporal pain). There was a greater frequency of cephalic allodynia, fatigue, disorders of mood and sleep in the group with fibromigraine in relation to the group with migraine alone. We concluded that there is a continuum between individuals with migraine and those with fibromigraine. In women with migraine the presence of fibromyalgia syndrome increases the frequency of fatigue, disorders of mood and sleep and tactile cephalic allodynia.